Clustering of Iron Oxide Nanoparticles with Amphiphilic Invertible Polymer Enhances Uptake and Release of Drugs and MRI Properties. (20th May 2019) - Price, Paige M.; Dittmar, Jasper W.; Carlson, Kenneth; Lawson, Bret P.; Reilly, Austin K.; Stein, Barry D.; Cheng, Hu; Zholobko, Oksana; Kohut, Ananiy; Voronov, Andriy; Bronstein, Lyudmila M.
Abstract: A functionalization of iron oxide nanoparticles (NPs) of different diameters by the amphiphilic invertible polymer, (PEG600‐ alt ‐PTHF650) k (PEG and PTHF stand for poly(ethylene glycol) and poly(tetrahydrofuran), respectively), leads to different NP/polymer architectures for dye/drug uptake and release, as is reported here for the first time. It is demonstrated that 18.6 ± 1.4 and 11.9 ± 0.6 nm NPs are individually coated by this polymer, while 5.9 ± 0.6 nm NPs form nanoparticle clusters (NPCs) which could be isolated by either ultracentrifugation or magnetic separation. This phenomenon is most likely due to the character of the (PEG600‐ alt ‐PTHF650) k macromolecule with alternating hydrophilic and hydrophobic fragments and its dimensions sufficient to cause NP clustering. Utilizing Rhodamine B base (RBB) and doxorubicin (DOX), the data on uptake upon mixing and further release via inversion into octanol (mimicking the penetration of the cell biomembrane) are presented. The magnetic NPCs display enhanced uptake and release of both RBB and DOX most likely due to the higher retained polymer amount. The NPCs also display exceptional magnetic resonance imaging properties. This and the high uptake/release efficiency of the NPCs combined with easy magnetic separation make them promising for theranostic probes for magnetically targeted drug delivery. Abstract : The amphiphilic invertible polymer, (PEG600‐ alt ‐PTHF650) k (PEG and PTHF stand for poly(ethylene glycol) and poly(tetrahydrofuran), respectively), coats hydrophobic iron oxide nanoparticles creating an invertible cargo space for dye/drug uptake and release. Depending on the nanoparticle size, the polymer coats nanoparticles individually or creates nanoparticle clusters, whose magnetic resonance imaging properties and drug uptake and release are superior compared to those of individually coated particles.